Preparation Technique Affects Recipient Immune Targeting of Autologous Mesenchymal Stem Cells - Rowland, Aileen L.; Burns, Madison E.; Levine, Gwendolyn J.; Watts, Ashlee E. (Frontiers in Veterinary Science, 2021)
Fetal bovine serum (FBS) is used for MSC preparation in pre-clinical animal models and veterinary applications, recently in US clinical trials, and for MSC products with current foreign market authorizations. The effect of anti-bovine titers, which are common in animals and humans, has not been investigated. In the equine model, where anti-bovine titers are universally high due to routine vaccination, we evaluated the recipient immune response to autologous MSCs prepared with and without FBS. Preparation of MSCs with FBS resulted in post injection inflammation and antibody mediated cytotoxicity of MSCs when compared to MSCs prepared without FBS. Importantly, synovial MSC concentrations were reduced and LPS induced pain was higher, when FBS was used to prepare MSCs, demonstrating reduced efficacy of FBS prepared MSCs. Fetal bovine serum should no longer be utilized for MSC preparation in pre-clinical study, clinical study, or veterinary applications. The use of FBS in previously reported studies, and in MSC therapeutics with current foreign market authorization, should be considered when interpreting results.